A simple and novel effective strategy using mechanical treatment to improve the oxygen uptake/release rate of YBaCo4O7+δ for thermochemical cycles. (30th March 2021) - Chen, Tingru; Asakura, Yusuke; Hasegawa, Takuya; Motohashi, Teruki; Yin, Shu
Abstract: In recent years, oxygen storage materials (OSMs) have been widely used in many fields. It would be particularly important for researchers to design high-oxygen-uptake/release-rate materials. In this study, various synthesis processes were used to successfully synthesize YBaCo4 O7+δ and comprehensively investigate their potential applications. Compared with traditional solid-state reaction method and co-precipitation method, the results demonstrated that the utilization of mechanical ball milling treatment on co-precipitated precursors could lead to samples with reversible oxygen uptake/release under an oxidative atmosphere at low temperatures. The resultant materials exhibited fast oxygen absorption/desorption rate that could uptake/release oxygen directly to the equilibrium state within 9 min and 20 min, respectively. The mechanochemically ball-milled sample possessed outstanding oxygen storage performance, which could be attributed to their small particle size, the active outer surface of particles, large specific surface area, and relatively low activation energy. Moreover, the ball-milled sample also exhibited excellent cycling stability during relatively short time spacing. TG results also demonstrated that the ball-milled samples could reversibly uptake/release 2.90 wt.% of excess oxygen (while only 0.70 wt.% for solid-state samples) by adjusting the ambient temperature under pure O2 atmosphere, which would make them promising candidates in various applications. This research demonstrated that mechanical treatment could be an effective strategy to tune the properties and oxygen storage capacity(OSC) performances of YBaCo4 O7+δ.